IMPROVING EFFICIENCY IN PRE-ECLAMPSIA DIAGNOSIS: SPOT URINARY PROTEIN/CREATININE RATIO - SINGH, PRAVEEN; ARNOTE, POOJA; THAKUR, KAJAL (International Journal of Current Pharmaceutical Research, 2024)
Objective: Because pre-eclampsia can cause difficulties, it presents a serious threat to maternal healthcare. The well-being of both the mother and the fetus depends on a prompt and precise diagnosis. There are drawbacks to using conventional techniques, such as collecting urine for a whole day to determine proteinuria. Although the spot urine protein/creatinine ratio is a faster option, its clinical value is yet unknown. Methods: The purpose of this cross-sectional study, which ran from July 1, 2018, to June 30, 2019, was to evaluate the spot urine protein/creatinine ratio in preeclamptic pregnant women vs the traditional 24 h urine protein collection technique. Ninety inpatients in all who satisfied certain inclusion and exclusion criteria were included. Results: Compared to comparable research by Hanumant et al. (13%), 6.66% of patients in our study had abnormal fundus examination findings. Papilloedema was absent from all participants, and the cautious management of anomalies was consistent across investigations. In line with the results of Hossain et al. and Sapna et al., the mean urine protein creatinine ratio in our investigation was 1.75±2.32. A smaller ratio was discovered by Umran et al., whereas Jung Hwa Park et al. claimed a larger ratio. Jung Hwa Park et al. also showed a greater mean protein excretion during a 24 h period (2713±2003 mg/d). Conclusion: This research at Kamla Nehru Hospital emphasizes the spot urine protein/creatinine ratio's potential as an effective pre-eclampsia diagnostic tool. In healthcare settings with limited resources, prompt detection of severe proteinuria can improve maternal and fetal outcomes by streamlining patient treatment.